KUTUKAN MENJADI BATU PADA LIMA LEGENDA DI INDONESIA - Dewi Juliastuty (Balai Bahasa Kalimantan Barat, 2018)
The purpose of the study was to describe the curse of being a stone in five legends in Indonesia. The problem of this research is how do curses become stones in five legends in Indonesia? This study uses the theory of oral literature with the method of descriptive analysis method. The conclusions of this study, namely the curse in the five Indonesian legends, is the influence of the totality of thinking that there is greater power beyond human power so that objects outside human beings have a unified relationship with humans.